Trends in Cyber-Physical Multi-Agent Systems. The PAAMS Collection - 15th International Conference, PAAMS 2017 - De la Prieta, Fernando; Vale, Zita.; Antunes, Luis.; Pinto, Tiago; Campbell, Andrew T.; Julián, Vicente; Neves, Antonio J.R.; Moreno, María N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
PAAMS, the International Conference on Practical Applications of Agents and Multi-Agent Systems is an evolution of the International Workshop on Practical Applications of Agents and Multi-Agent Systems. PAAMS is an international yearly tribune to present, to discuss, and to disseminate the latest developments and the most important outcomes related to real-world applications. It provides a unique opportunity to bring multi-disciplinary experts, academics and practitioners together to exchange their experience in the development of Agents and Multi-Agent Systems. This volume presents the papers that have been accepted for the 2017 in the special sessions: Agent-Based Social Simulation, Modelling and Big-Data Analytics (ABM); Advances on Demand Response and Renewable Energy Sources in Agent Based Smart Grids (ADRESS); Agents and Mobile Devices (AM); Computer vision in Multi-Agent Robotics (RV); Persuasive Technologies (PT); Web and Social Media Mining (WASMM). Thevolume also includes the papers accepted for publication in the Doctoral Consortium (DCAI, DCAI-DECON, ISAMI, MIS4TEL, PAAMS, PACBB 2017 conferences).
Acceleration of Dissimilarity-based Classification Algorithms using Multi-core Computation -- A Study on IoT Technologies in Smart Cities (An Exploratory Study in India) -- Malware Propagation Software for Wireless Sensor Networks -- New perspectives in the study of Advanced Persistent Threats -- Towards Modelling Organisational Dynamics for Large-Scale Multiagent Systems -- On the optimal NFVI-PoP placement for SDN-enabled 5G networks Active ageing agents -- Pattern extraction for the design of predictive models in Industry 4.0 -- Rethinking posts through emotion awareness -- Self-healing mechanism over the cloud on interaction layer for AALs using HARMSChallenges in Smart Spaces: Aware of users, preferences, behaviours and habits. Decision support for smart grid planning and operation considering reliability and all available resources -- An actor-based bottom-up simulation aid for complex dynamic decision making -- µGIM - Microgrids Intelligent Management System Based on a Multi-agent Approach and the Active Participation on Demand Response -- Organization-based Multi-Agent System of Local Electricity Market: Bottom-Up Approach Remuneration and Tariffs in the Context of Virtual Power Players.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence